2014
DOI: 10.2139/ssrn.2507207
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect of Scholarships Targeted at Low Income Students on Performance: Evidence from Italy

Abstract: This paper exploits discontinuities in the assigment of scholarships targeted at low income students in an Italian University in order to evaluate the effects of monetary incentives on students' academic achievement. Results reveal positive and sizeable causal effects both in terms of credits and grades. Gender differentials also emerge: male students drive the results on credits outcome while females students drive the effect on grades. These results suggest that the scholarship design contributes to reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In other words, the results of these research support findings that scholarship or financial factors can increase retention and completion of study [9], and is a predictor of student success in higher education. [12] The scholarships provided for less economic capacity students, could not only respond to the purpose or promote equity of access to higher education, but they could also be used as active tools to boost students performances. [13] With the scholarship benefits above, then it is natural when most student scholarship awardee have a high learning motivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the results of these research support findings that scholarship or financial factors can increase retention and completion of study [9], and is a predictor of student success in higher education. [12] The scholarships provided for less economic capacity students, could not only respond to the purpose or promote equity of access to higher education, but they could also be used as active tools to boost students performances. [13] With the scholarship benefits above, then it is natural when most student scholarship awardee have a high learning motivation.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The research found that provision of financial assistance contribute to increase HE student retention and completion, [11] or contribute to a reduction in the likelihood of delay of graduation. [12] Thus financial aid can be a strong predictor of student persistence, progression, and timely graduation, [13] as well as student success in higher education. [9] The research results showed that student scholarship awardee can achieve a higher achievement than non-scholarship awardee or regular students.…”
Section: Literature Reviewmentioning
confidence: 99%